1994
DOI: 10.1016/0014-5793(94)80290-4
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin gene expression is increased in skeletal muscle of tumour‐bearing rats

Abstract: Rats bearmg the fast-growmg AH-l 30 Yoslnda ascItes hepatoma showed a marked cachectlc response which has been previously reported [Tessltore et al (1987) Blochem J 241, 153-1591 Thus tumour-bearmg ammals showed slgmficant decreases m body and muscle weight (soleus and gastrocnemms) as compared to both pair-fed and ad hbltum-fed animals These decreases were related to an enhanced proteolytlc rate m the muscles of the tumour-bearmg ammals as measured by the tyrosme released m m vitro assays In an attempt to elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(79 citation statements)
references
References 53 publications
3
75
0
1
Order By: Relevance
“…As previously shown (Llovera et al, 1994), the accelerated muscle protein breakdown in the AH-130 hosts is associated with activation of the ATP-ubiquitin-dependent proteolytic system. Two polyubiquitin mRNA species (2.4 kb and 1.2 kb) were found in tibialis muscle (Figure 1).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…As previously shown (Llovera et al, 1994), the accelerated muscle protein breakdown in the AH-130 hosts is associated with activation of the ATP-ubiquitin-dependent proteolytic system. Two polyubiquitin mRNA species (2.4 kb and 1.2 kb) were found in tibialis muscle (Figure 1).…”
Section: Resultssupporting
confidence: 55%
“…Recently, this proteolytic system has been involved in the perturbations of protein metabolism in skeletal muscle in many pathological conditions (see Argilés and López-Soriano, 1996 for review). Previous studies from our laboratory have shown that the lysosomal pathway is only marginally involved in the development of muscle protein hypercatabolism in the AH-130 hosts (Llovera et al, 1994;Tessitore et al, 1994), while an important activation of the ATP-dependent proteolysis seems to be the major mechanism (Llovera et al, 1994;Costelli et al, 1995). It is very interesting to observe that the preventive effect exerted by IL-15 on the acceleration of muscle protein breakdown is associated with a normalization of the hyperexpression of both the C8 proteasome subunit and the ubiquitin mRNAs.…”
Section: Discussionmentioning
confidence: 80%
“…Nevertheless, we cannot rule out the possibility that other pathways that we did not examine may have been activated by circulating TNF-α in aging muscles. For example, TNF-α has been shown to directly promote protein degradation [33][34][35][36] and apoptosis [37] within skeletal muscle. Furthermore, intravenous injection of recombinant TNF-α increases protein degradation in rat skeletal muscles and this is associated with the increased activity of the ubiquitin-dependent proteolytic pathway [33,34,36,38].…”
Section: Effects Of Tnf-α In Skeletal Musclementioning
confidence: 99%
“…For example, TNF-α has been shown to directly promote protein degradation [33][34][35][36] and apoptosis [37] within skeletal muscle. Furthermore, intravenous injection of recombinant TNF-α increases protein degradation in rat skeletal muscles and this is associated with the increased activity of the ubiquitin-dependent proteolytic pathway [33,34,36,38]. In addition, elevated TNF-α concentrations in cell culture for 24-48 h increases apoptosis in skeletal myoblasts as determined by DNA fragmentation [39,40].…”
Section: Effects Of Tnf-α In Skeletal Musclementioning
confidence: 99%
“…The same proteolytic pathway has been implicated in muscle breakdown caused by denervation (11), fasting (12), acidosis (13), cancer (14), and burn injury (15).…”
Section: Introductionmentioning
confidence: 99%